Genetically encoded phenyl azide photochemistry drives positive and negative functional modulation of a red fluorescent protein12. Issue 95 (15th October 2015) - Reddington, Samuel C.; Driezis, Sarunas; Hartley, Andrew M.; Watson, Peter D.; Rizkallah, Pierre J.; Jones, D. Dafydd
<x xml:space="preserve">Abstract</x> Genetically encoded incorporation of phenyl azide chemistry into the autofluorescent protein mCherry can be used to switch on or off fluorescence.